The perspective of Arabic Muslim women towards sport participation - Abdul Razak, Maesam T.; Omar Fauzee, Mohd Sofian; Abdul Latif, Rozita (JAPSS Press, 2010)
The purpose of this study is to examine perspective of Arabic Muslim women toward the involvement in sport and physical activity. A sample of 15 Arabic Muslim women (age between 14 to 30 years old) who sojourn in Malaysia (i.e., studying, visiting, or housewife) have agreed to participate in the interview. All of them have signed an informed consent letter to be tape recorded. The recorder interviews were transcript and content analysis processes were conducted to identify the answers given in the semi structured questionnaire. Result shows that the women in this study are strongly influenced by the processes of cultural maintenance and identify with their parent’s ethnic group. Twelve Arabic Muslim women from 15 belong to different Arabic countries answered on question 3 with negative aspect as an example of the women who positions themselves clearly within the framework of their ethnic identity. The participating for the young Arabic Muslim woman in sport is seen as a challenge to the boundaries of their ethnic identities.The young Arabic Muslim women who position themselves clearly within the framework of their ethnic identities are not interested in sport because doing sport is not seen as a respectable femininity. Perhaps, these Arabic Muslim women who challenge their ethnic identities by participating in sport have experienced being harassed because they participate in sport. Recommendations for future research were also suggested in this paper.